Issues in teaching numeracy in primary schools - Thompson, Ian; Thompson, Ian (Frederick Ian) (McGraw-Hill, Open University Press, 2010)
Issues in Teaching Numeracy in Primary Schools, 2e presents an accessible guide to current British and Dutch research into numeracy teaching.